Blood-flow-restricted exercise: Strategies for enhancing muscle adaptation and performance in the endurance-trained athlete - Ferguson, R. A.; Mitchell, E. A.; Taylor, C. W.; Bishop, D. J.; Christiansen, D. (Experimental Physiology, 2021)
What is the topic of this review?